Development of a User Oriented Optimization System For Computer Aided Design Packages. - Jha, Virendra Kumar (My University, 1971)
A new user oriented optimization system is described which is particularly useful for integration into user oriented design packages. Four new subroutines have been developed for the system, one being for integer or mixed integer nonlinear problems. A description is given of the problem of handling constraints while solving optimization problems. The technique of integration into a design package is discussed. Solutions of four sample problems have been included to demonstrate use of the subroutines.
Keywords: user oriented; optimization system; computer aided design package; subroutine